Морфологічні показники продихів і склад кутикулярних восків листків липи повстистої (Tilia tomentosa Moench) за умов освітлення та затінення - Lykholat, Yu.V.; Khromykh, N.O.; Alekseeva, A.A.; Serga, O.I.; Yakubenko, B.E.; Grigoryuk, I.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to determine the differences in the morphological parameters of stomata and the component composition of cuticular waxes of silver linden (Tilia tomentosa Moench) leaves under conditions of lighting and shading in the crown of a tree. Material and methods. The sun-adapted and shadeadapted fully developed leaves of silver linden were selected as the test objects in our study. The component composition of the cuticular waxes was investigated by gas chromatography method, and stomata size and quantity values were determined on the epidermal imprints of the abaxial side of leaves. Results. The adaptive changes in leaves of the alien invasive plant species silver linden were established under conditions of increasing light intensity and temperature and reducing air humidity. Conclusion. The leaf surface area, leaf weight per unit area, density of stomata, and the content of the long chain components of the cuticular waxes increase, the length and the width of stomata decrease under conditions of lighting.